2007
DOI: 10.1177/089686080702700612
|View full text |Cite
|
Sign up to set email alerts
|

Serum BNP Concentration and Left Ventricular Mass in CAPD and Automated Peritoneal Dialysis Patients

Abstract: Objective To compare ultrafiltration under continuous ambulatory peritoneal dialysis (CAPD) and automated PD (APD), disclosing potential effects on serum B-type natriuretic peptide (BNP) levels and echocardiographic findings. Patients and Methods This cross-sectional clinical study included 32 patients on CAPD and 30 patients on APD without clinical evidence of heart failure or hemodynamically significant valvular heart disease. Peritoneal equilibration tests, BNP levels, and echocardiographic measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…However, it remains inconclusive and needs more researches [ 186 ]. Meanwhile, due to reduced ultrafiltration rate, continuous volume overload and more LV hypertrophy, patients with automated PD (APD) may have higher BNP levels than those with continuous ambulatory PD (CAPD) [ 187 ]. Moreover, plasma BNP levels have a significant potential to identify LV hypertrophy or dysfunction in patients with different dialysis and renal transplant [ 188 190 ].…”
Section: Diagnostic Valuesmentioning
confidence: 99%
“…However, it remains inconclusive and needs more researches [ 186 ]. Meanwhile, due to reduced ultrafiltration rate, continuous volume overload and more LV hypertrophy, patients with automated PD (APD) may have higher BNP levels than those with continuous ambulatory PD (CAPD) [ 187 ]. Moreover, plasma BNP levels have a significant potential to identify LV hypertrophy or dysfunction in patients with different dialysis and renal transplant [ 188 190 ].…”
Section: Diagnostic Valuesmentioning
confidence: 99%
“…and Bavbek et al . examined the incidence of left ventricular mass index (LVMI) in APD and CAPD patients [ 74 , 75 ]. Wang et al .…”
Section: Residual Renal Function–blood Pressure–ultrafiltration–sodiumentioning
confidence: 99%
“…included 32 CAPD and 30 APD patients without clinically evident cardiovascular or valvular heart disease. They also revealed a higher LVMI in APD compared to CAPD patients [ 75 ]. Yet, Jang et al .…”
Section: Residual Renal Function–blood Pressure–ultrafiltration–sodiumentioning
confidence: 99%
“…However, since BNP levels remain elevated after significant fluid loss after each dialysis session in both HD patients, other factors must also be involved 27 . Bavbek et al, 29 and Sanjuan et al, 27 found that there was a good correlation between BNP and LVMI, with LVMI being the most significant factor indicating the BNP increase. Sanjuan et al, 27 concluded that in asymptomatic patients, marked increases in BNP levels may reflect very early stages of pathological processes that precede the development of apparent cardiac signs (such as measurable LVH) in patients on extrarenal dialysis.…”
Section: Discussionmentioning
confidence: 99%